2016
DOI: 10.3111/13696998.2016.1159567
|View full text |Cite
|
Sign up to set email alerts
|

The association between osteoporosis and patient outcomes in Japan

Abstract: Objective To quantify the burden of osteoporosis and examine the interplay between osteoporosis and various comorbidities as it relates to patient outcomes. Methods Data from the 2011 Japan National Health and Wellness Survey (NHWS; n = 30 000), an internet health survey fielded to a nationally representative sample of the Japanese population were used. Only women between the ages of 50-90 years were included in the analyses (n = 6950). Results Compared with matched controls (n = 404), patients with osteoporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Prevalence among women trended higher than among men in every age group and also appeared to increase with age [ 54 , 55 , 58 , 59 ], although few estimates were found for women under 50. Broad age group estimates of 40 + or 50 + had a wide prevalence range as well, from 5.8% to more than 40% [ 60 , 61 ]. Narrower age group prevalence estimates suggested that after the age of 50, prevalence (starting below 10% in ages 50–59) grew 10–20% with each decade of life [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence among women trended higher than among men in every age group and also appeared to increase with age [ 54 , 55 , 58 , 59 ], although few estimates were found for women under 50. Broad age group estimates of 40 + or 50 + had a wide prevalence range as well, from 5.8% to more than 40% [ 60 , 61 ]. Narrower age group prevalence estimates suggested that after the age of 50, prevalence (starting below 10% in ages 50–59) grew 10–20% with each decade of life [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Osteoporosis is a chronic bone disease with low bone mineral density (BMD) which may cause fragility fractures, disability and decrease the quality of life. One third and one fifth of women and men, respectively, aged over 50 years, suffer an osteoporotic fracture [9][10][11]. The ageing of the population causes an increase in the number of people who suffer from osteoporosis-it is estimated that nowadays 200 million people report this disorder [12].…”
Section: Introductionmentioning
confidence: 99%